Kerala's Changing Development Narratives - ACHIN CHAKRABORTY (ACHIN CHAKRABORTY, 2005)
The popular development narrative for Kerala suggests that the state's experience throws up issues that are expected to inform policy-makers elsewhere, in their endeavour to achieve human development goals within the constraints set by modest economic expansion. The positive tone of this narrative was somewhat subdued in the 1990s by the growing literature on the problem of `sustainability', and the `crisis' potential of the so-called Kerala model. The crisis narrative now seems to be giving way to an emerging one of economic growth that might have indirect links with the state's earlier achievements in education and health. In this paper, an attempt has been made to present Kerala's recent development experience in terms of a couple of identifiable narratives, instead of a singular `fact'.